Retrospective evaluation of Vitis vinifera ingestion in dogs presented to emergency clinics in the UK (2012–2016): 606 Cases. Issue 1 (31st October 2020) - Croft, Rachel; Clementi, Elisabetta; Farmer, Helen; Whalley, Rachel; Dunning, Mark; Firth, Ava
Abstract: Objective: To assess key presenting signs in dogs following Vitis vinifera fruit (VVF) ingestion (grapes, raisins, currants, and sultanas), outcome, and the incidence of acute kidney injury (AKI). Design: Retrospective study (2012–2016). Setting: Out‐of‐hours clinics in the United Kingdom. Animals: The study population included 606 dogs attending 53 emergency clinics across the United Kingdom following ingestion of VVF. Interventions: None. Measurements and Main Results: Vitis vinifera fruits were found in vomit after more than 12 hours after ingestion. There was an increased incidence in December. Serum creatinine or urea was measured in 338 dogs; all were within reference intervals. In this cohort of dogs with VVF ingestion, there is no evidence for significant AKI in 32 of 33 cases within 24 hours of admission where supportive measures were introduced and repeated assessments of creatinine concentration were performed. Conclusions: All dogs survived to discharge. One out of 33 cases with repeated creatinine concentration developed IRIS AKI grade I within 24 hours following VVF ingestion, when current emergency treatment guidelines were followed in whole or part.